Intercultural Jakarta, Ambience of Betawi Theatre to Indonesian Theatre - Julianti Parani (Wacana Seni Journal of Arts Discourse, 2006)
It is naturally taken for granted that the intercultural role of Jakarta has opened opportunities for the development of contemporary Indonesian theatre and performing arts. We need to take into consideration some significant benchmarks of the Dutch colonial impact in the city of Batavia or colonial Jakarta such as the Asian cultural impact before discussing further. In particular, Chinese and indigenous Betawi cultures of Jakarta contributed to a collage of nationalistic expression in the arts, which formed a prologue to the embryonic features of Indonesian theatre expression. We must also acknowledge Taman Ismail Marzuki (TIM) and the Jakarta Arts Centre for showcasing and exposing artists to all these arts.